BEBERAPA FAKTOR RISIKO KEJADIAN HIPERTIROID PADA WANITA USIA SUBUR DI KABUPATEN MAGELANG â€œStudi Kasus di Klinik Litbang BP2GAKI Magelangâ€ - Sari, Erent Ersantika; Susanto, Henry Setyawan; Udiyono, Ari; Suwandono, Agus (Jurnal Kesehatan Masyarakat (e-Journal), 2015)
Hyperthyroidism is the condition that occurs due to excessive production of thyroid hormone by thyroid gland which increased the levels of fT4, T4, fT3, and decreased TSH. The results of RISKESDAS showed that the proportion of household iodine suplementation increased to 5% in 2013. This can eventually leads to hyperthyroidism. Last screening by Magelang District Health Department showed that there is 16,67 % cases of Hyperthyroidism in 2013. The purpose of this research is to analyze some risk factors of hyperthyroidism in fertile age women in Magelang District. This research use analytical observation with cross sectional comparative design with 100 sample in endemic area and 54 in non endemic area of GAKI (Iodine deficiency disorders). Logistic Regression was used to analyze data with significance level of 5 %. The results of multivariate analysis showed in endemic GAKI areas, the consumption of iodine capsule (pOR=10,6 p=0,001), stress level (pOR = 8,4 p=0,001), high iodine food (pOR=5,8 p=0,007), iodine salt > 30 ppm (pOR=6,9 p=0,002) and smoke exposure (pOR=4,1 p=0,030) were risk factors of hyperthyroidism. Despite, hormonal contraception (pOR=8,0 p=0,007) was not a risk factor of hyperthyroidism. The results of multivariate analysis showed in non endemic GAKI areas, stress level ( pOR = 11.2 p = 0.002 ) and high iodine food (pOR = 8.0 , p = 0.007 ) were risk factors of hyperthyroidism. Despite, iodine salt > 30 ppm , hormonal contraception , the consumption of iodine capsule, and smoke exposure have P value ≥ 0.05 so it was not a risk factors of hyperthyroidism in Magelang District. The results of multivariate analysis showed in Magelang Distric, stress level ( pOR = 41,1 p ≤ 0,0001 ), high iodine food (pOR = 11,2 p ≤ 0.0001), smoke exposure (pOR=3,5 p=0,037) and the consumption of iodine capsule(pOR =4,97 p=0,016) were risk factors of hyperthyroidism. Despite, iodine salt > 30 ppm and hormonal contraception have P value ≥ 0.05 so it was not a risk factors of hyperthyroidism in Magelang District.